1978
DOI: 10.1104/pp.62.4.571
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Specificity and Site of Action of α-Cyclopropyl-α-[p-methoxyphenyl]-5-pyrimidine Methyl Alcohol (Ancymidol), a Plant Growth Regulator

Abstract: a-Cyclopropyl-a-Ip-methoxyphenyll-5-pyrimidine methyl alcohol (ancymidol) is an inhibitor of ent-kaur-16-ene oxidation in microsomal preparations from the liquid endosperm of immature Marab macrocarpus seeds. The Ki for this inhibitor is about 2 x 10-9 M. Ancymidol also blocks entkaur-16-en-19-ol and ent-kaur-16-en-19-al oxidation by the same preparations with a similar efficiency, but does not significantly inhibit ent-kaur-16-en-19-oic acid oxidation. Ancymidol appears to be specific for this series of oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(35 citation statements)
references
References 18 publications
2
32
0
1
Order By: Relevance
“…Similar treatment of the gibberellin insensitive double-dwarf mutants had no significant effect. Ancymidol, a potent inhibitor of gibberellin biosynthesis (5), decreased plastic extensibility of both the tall and semidwarf genotypes, by 71 and 69%, respectively, but had no significant effect on the double dwarf genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Similar treatment of the gibberellin insensitive double-dwarf mutants had no significant effect. Ancymidol, a potent inhibitor of gibberellin biosynthesis (5), decreased plastic extensibility of both the tall and semidwarf genotypes, by 71 and 69%, respectively, but had no significant effect on the double dwarf genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Other data also support the proposal that the oxidation of ent-kaurene to ent-kaurenoic acid is catalyzed by a single enzyme. Coolbaugh et al (1978) showed that in wild cucumber (Marah macrocarpus) the inhibition of each of the three steps from ent-kaurene to ent-kaurenoic acid by ancymidol had the same kinetics, whereas inhibition of oxidation of ent-kaurenoic acid to ent-7␣-hydroxykaurenoic acid was greater, suggesting that it is catalyzed by a different enzyme.…”
mentioning
confidence: 99%
“…The structural feature common to all these inhibitors of ent-kaurene oxidation is a lone electron pair on the sp 2 -hybridised nitrogen of their heterocyclic ring. In each case, this electron pair is located at the periphery of the molecule (Rademacher et al, 1987) and it appears likely that it displaces oxygen from its binding site at the protoheme iron (Coolbaugh et al, 1978). Evidence for such a type of interaction has been presented for ancymidol in microsome preparations of Marah macrocarpus (Coolbaugh and Hamilton, 1976;Coolbaugh et al, 1978) and for BAS 111..W …”
Section: Compounds With a Nitrogen-containing Heterocyclementioning
confidence: 88%